Implementation of Online Learning on Teachers's and Students's Perspective in Indonesia - Susiawati, Wati (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2021)
This article is the result of observations made by the author on the Webinar participants by distributing Google forms to them with the restrictions on the Covid 19 period, namely from the beginning of Covid 19 until the webinar was held on 18th. July 2020. The total of 1.401 participants signed up, 767 of who attended via zoom meeting and youtube. The participants came from various universities in Indonesia. There are 390 students (51,05%), 178 lecturers (23,30%), 189 teachers (24,74%), and 7 students (0,92%). As a result, it was noted that 42.1% of the lecturers conducted Online Learning between 6-10 meetings and 37.7% of students attended Online Learning for more than 11 meetings. In terms of implementing Online Learning, the majority of them answered that they preferred normal learning than Online Learning as evidenced by the results of their answers, namely lecturers 85.4%, students 93.1%, teachers 89.9%, while students 100% answered the same.